2005
DOI: 10.1210/jc.2005-0167
|View full text |Cite
|
Sign up to set email alerts
|

Early Atherosclerosis in Obese Juveniles Is Associated with Low Serum Levels of Adiponectin

Abstract: In summary, our study describes an influence of SAT topography on adiponectin serum levels and provides first evidence that incipient atherosclerosis is associated with low serum levels of this adipocytokine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
110
3
8

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 162 publications
(128 citation statements)
references
References 39 publications
7
110
3
8
Order By: Relevance
“…Similarly, low levels of adiponectin are mechanistically linked to increased clearance rate of HDL-C (i.e., reduced numbers of this lipoprotein) 25 and are associated with increased progression of coronary artery calcium in adults 11 and increased carotid intima media thickness in children. 15 Moreover, hypoadiponectinemia is associated with visceral adiposity, insulin resistance, b-cell dysfunction, component factors of the metabolic syndrome, and inflammation in children and adolescents. 9,13,14,18,19,23 Together, these data suggest that leptin and adiponectin may play prominent roles in the early disease processes of type 2 diabetes mellitus and cardiovascular disease and abnormal levels of these adipokines in childhood may reflect increased risk for developing these chronic diseases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, low levels of adiponectin are mechanistically linked to increased clearance rate of HDL-C (i.e., reduced numbers of this lipoprotein) 25 and are associated with increased progression of coronary artery calcium in adults 11 and increased carotid intima media thickness in children. 15 Moreover, hypoadiponectinemia is associated with visceral adiposity, insulin resistance, b-cell dysfunction, component factors of the metabolic syndrome, and inflammation in children and adolescents. 9,13,14,18,19,23 Together, these data suggest that leptin and adiponectin may play prominent roles in the early disease processes of type 2 diabetes mellitus and cardiovascular disease and abnormal levels of these adipokines in childhood may reflect increased risk for developing these chronic diseases.…”
Section: Discussionmentioning
confidence: 99%
“…8 Leptin and adiponectin, two of the most abundant adipokines secreted from adipocytes, have been implicated in the development of type 2 diabetes mellitus and cardiovascular disease [9][10][11][12] and are associated with metabolic syndrome, visceral adiposity, insulin resistance, b-cell dysfunction, inflammation, arterial stiffness, and subclinical atherosclerosis in children. 9,[12][13][14][15][16][17][18][19] Leptin plays a prominent role in energy metabolism through its interaction with the hypothalamus and, in the context of obesity, leptin is often produced in high quantities due to leptin resistance. 20 Importantly, leptin is an independent predictor of future weight-gain in obese youth.…”
Section: Introductionmentioning
confidence: 99%
“…In our study, we found that carotid IMT was significantly and inversely related with the serum concentrations of adiponectin. Similarly, a negative correlation between adiponectin levels and carotid IMT has been reported in obese juveniles 16) and in patients with coronary artery disease. 17) However, in our study, adiponectin levels were not significantly correlated with either the atherosclerotic carotid plaque thickness or the plaque length.…”
Section: Discussionmentioning
confidence: 58%
“…22- 24 Okamoto et al reported that allografts transplanted into APN-deficient mice showed severe acute rejection relative to transplantions in wild-type mice, and provision of APN by adenovirus in APN-deficient mice reversed these exacerbated responses to allografting. 25 However, their study did not show a difference in cardiac allograft survival in APN-deficient mice.…”
Section: Discussionmentioning
confidence: 99%